Markers of Myocardial Ischemia in Patients With Coronary Artery Disease and Obstructive Sleep Apnea: Effect of Continuous Positive Airway Pressure Therapy. Issue 8 (14th July 2015) - Valo, Misa; Wons, Annette; Moeller, Albert; Teupe, Claudius
ABSTRACT Background Obstructive sleep apnea (OSA) is associated with an increased risk of cardiovascular complications. OSA and coronary artery disease (CAD) share the same risk factors and coexist in many patients. In previous studies, repeated nocturnal cardiac ischemic events in OSA patients with CAD have been reported. Hypothesis We hypothesized that OSA may precipitate myocardial ischemia, evidenced by ST‐segment depression and elevated N‐terminal brain natriuretic peptide (NT‐proBNP) and high‐sensitivity troponin T (hs‐TropT) levels in patients with severe OSA and concomitant CAD. We also aimed to evaluate if the effects could be reversed by continuous positive airway pressure (CPAP) therapy. Methods Twenty‐one patients with severe OSA (apnea‐hypopnea index >15/h, nadir oxygen desaturation ≤80%), and coexisting CAD underwent in‐hospital polysomnography at baseline and under CPAP. Blood samples for hs‐TropT and NT‐proBNP measurements were drawn prior and immediately after sleep. ST‐segment depression was measured at the time of maximum oxygen desaturation during sleep. Results CPAP significantly decreased elevated NT‐proBNP levels from 475 ± 654 pg/mL before sleep to 353 ± 573 pg/mL after sleep and attenuated ST‐segment depression during sleep. hs‐TropT was not elevated and did not differ after nocturnal oxygen desaturation at baseline and after CPAP. Conclusions CPAP significantly reduced NT‐proBNP in patients suffering from severe OSA and coexisting CAD. Repeated nocturnal myocardial ischemia did not cause myocyte necrosis evidenced by elevated hs‐TropT or ST‐segment depression.